Visit of Prime Minister Dr. Manmohan Singh to Japan 13-16 December 2006. - Manmohan Singh 1932- (Public Diplomacy Division, Ministry of External Affairs, Government of India, 2007)
Transcript of speeches delivered during his Japan visit.